A comparative study of ultrasound-guided caudal block versus anatomical landmark-based caudal block in pediatric patients undergoing infra-umbilical surgeries - Suman Halder; Amrita Roy; Payel Mitra; Maitreyee Mukherjee; Arpita Laha (Asian Journal of Medical Sciences)
Background: Pain is an unpleasant sensory and emotional experience that can lead to a variety of potentially negative sequelae in any age group. Thus, efficient and optimum pain management is essential. Optimum post-operative pain management is crucial for preventing adverse sequelae in the post-operative period. Caudal epidural block is a commonly performed regional anesthetic technique for maintaining intra- and post-operative analgesia for pediatric patients undergoing lower abdominal, urogenital, and lower limb surgeries.